Evaluating Cryptocurrency Through Islamic Law: Ethical Advantages and Economic Benefits - Nameer Hashim Qasim (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2026)
The article deals with the ongoing legal and ethical controversy on the ability of cryptocurrency to be reconciled with the concept of Islamic finance, especially the fact that riba, garar, and maysir are forbidden, and that transparency, justice, and the common good must be upheld. The article aimed to understand the permissibility of cryptocurrency in the Islamic law context based on the jurisprudential component, technical transparency, market stability, decentralized compliance capacity, and socio-economic utility. The article used normative juridical research that was subject to comparative analytical framework, which combined doctrinal Islamic legal analysis with technical and economic indicators. Moreover, it was based on five dimensions: jurisprudential evaluation, blockchain transparency, volatility and stability, decentralized compliance, and economic utility. The results indicated that cryptocurrency cannot be either categorized as halal or haram; instead, its Shariah is conditional and asset-based. Stellar exhibited the best jurisprudential alignment, Cardano and Ethereum delivered the most successful results in transparency indicators, Solana and Bitcoin had a comparably more stable risk profile, Ethereum and Polygon had the best decentralized compliance capability, and Celo and Stellar had the best inclusion and efficiency results. The article found out that cryptocurrency must not be permitted or prohibited in the Islamic law but rather by a multidimensional evaluation of its legal framework, design, market dynamics, and social-economic impact.